Quantification of dissolved and particulate radiocesium fluxes in two rivers draining the main radioactive pollution plume in Fukushima, Japan (2013–2016). (June 2018) - Osawa, Kazutoshi; Nonaka, Yui; Nishimura, Taku; Tanoi, Keitaro; Matsui, Hiroyuki; Mizogichi, Masaru; Tatsuno, Takahiro
Graphical abstract: Highlights: Continuous river monitoring was conducted for 3.5 years from 2013 to 2016. The time series of 137 Cs fluxes were represented. The annual mean 137 Cs concentration of SS decreased sharply in 2016. Redistribution of radiocesium was transported mainly by the particulate form. The ratios of 137 Cs export to the 137 Cs inventory deposited on soils were very low. Abstract: Radionuclides released by the accident at the Fukushima Daiichi Nuclear Power Plant included 137 Cs (Cesium-137) and 134 Cs (Cesium-134), which were deposited on land as a result of fallout and concentrated in the uppermost 2–5 cm of the soil. In this study, river monitoring was conducted for 3.5 years to quantify dissolved and particulate radiocesium fluxes in the Mano and Hiso Rivers in Fukushima Prefecture from 2013 to 2016. Total 137 Cs export was estimated to be 191 GBq from the Hiso River and 26 GBq from the Mano River during the 3.5-year study. Annual particulate 137 Cs export during rainfall events accounted for 90–98% of total 137 Cs export. Annual dissolved 137 Cs export during rainfall events accounted for 1.5–3.3% of total export. The annual sum of particulate and dissolved 137 Cs exports during low-flow periods accounted for 0.6–6.5% of total export. Hence, radiocesium was redistributed mainly by transport of particulate radiocesium bound to suspended sediments. During the study period, 0.7% and 0.6% of the 137 Cs initially deposited on soil were exported by the Hiso River and Mano River, respectively. The slopes of regression lines relating fine suspended sediment concentrations and particulate 137 Cs concentrations in river water declined from 2013 to 2016 by 79% for the Hiso River and 83% for the Mano River. Especially noteworthy was a sharp decrease of the annual mean 137 Cs concentration of SS in 2016. This decrease was much greater than the decrease that would have been expected from the physical decay of 137 Cs and was probably related to changes of soil erosion processes due to heavy rainfall and the effects of decontamination efforts in 2015.